Controversies and Unconstitutional Practices of Elections Postponement in Indonesia: State Interest or Political Elite Interest? - Rakia, A. Sakti R.S (Fakultas Hukum Universitas Muhammadiyah Sorong, 2024)
The Indonesian political atmosphere has recently been shocked by controversial issues regarding the postponement of the Indonesian elections in 2024 nationally. The reason for postponing the election is due to the unstable economic condition of the country after COVID-19 so that it is considered incapable of holding elections in 2024. This study aims to find out how the postponement of elections is regulated in Indonesia, as well as whether the postponement of elections is a constitutional action or for the interests of groups elite. The results of this study indicate that basically the Indonesian Election Law does not specifically regulate the postponement of elections. The postponement of elections in the provisions of election law in Indonesia only regulates regional election delays. Meanwhile, national election delays are not adequately regulated. Therefore, nationally postponing the election is considered a violation of the Indonesian constitution. In addition, it is seen that the postponement of the election is not an aspiration of the Indonesian people so that it is considered an attempt by the political elite to take political advantage in the 2024 election.